2019
DOI: 10.1080/14786419.2018.1544981
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and xanthine oxidase inhibitory activities of flavonoids from the leaves of Perilla frutescens

Abstract: Phytochemical investigation of the water extract from the leaves of Perilla frutescens (Lamiaceae) led to the isolation of a new flavanone, a new chalcone, and a new aurone, namely, (2S)-5,7-dimethoxy-8,4'-dihydroxyflavanone (1), 2',4'-dimethoxy-4,5',6'trihydroxychalcone (2), and (Z)-4,6-dimethoxy-7,4'-dihydroxyaurone (3), respectively.The structures were unambiguously elucidated on the basis of spectroscopic data. And the absolute configuration of 1 was determined by analysis of electronic circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Liu et al. isolated an Z type aurone derivative (Z)‐4,6‐dimethoxy‐7,4′‐dihydroxyaurone (as shown in Figure 4) from the leaves of Perilla frutescens , but found no apparent inhibitory activity against XO (Liu et al., 2019). However, the carboxylated aurone derivatives have been shown to be potent XO inhibitors.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Liu et al. isolated an Z type aurone derivative (Z)‐4,6‐dimethoxy‐7,4′‐dihydroxyaurone (as shown in Figure 4) from the leaves of Perilla frutescens , but found no apparent inhibitory activity against XO (Liu et al., 2019). However, the carboxylated aurone derivatives have been shown to be potent XO inhibitors.…”
Section: Flavonoidsmentioning
confidence: 99%
“…In 2015, Zhao et al reported that ingredients of Perillae Folium include rosmarinic acid, elemicin, perillaldehyde, and dillapiole [30]. It is well known that Perillae Folium contains a lot of polyphenols and flavonoids such as luteolin, 4-hydroxycinnamic acid, scutellarin, caffeic acid, apigenin, chrysoeriol, malvidin, cyanidin, and kaempferol [31][32][33] as well as triterpene acids such as antitumor-promoting tormentic acid [34]. Ueda et al reported in 2002 that oral administration of Perillae Folium extract to mice shows anti-inflammatory and antiallergic activity with inhibiting TNF-α production; luteolin isolated from Perillae Folium extract inhibits serum TNF-α production [35].…”
Section: Discussionmentioning
confidence: 99%
“…The flavanones in P. frutescens leaves include shisoflavanone A, liquiritigenin, 5,8-dihydroxy-7-methoxyflavanone, (2S)-5,7-dimethoxy-8,4′-dihydroxy flavanone, and 8-hydroxy-5,7-dimethoxyflavanone. The chalcones in P. frutescens leaves include 2′,4′-dimethoxy-4,5′,6′-trihydroxychalcone, and 2′,3′-dihydroxy-4′,6′-dimethoxychalcone, along with an aurone, (Z)-4,6-dimethoxy-7,4′-dihydroxyaurone [ 41 ].…”
Section: Phytoconstituents Of P Frutescensmentioning
confidence: 99%
“…A chalcone,2′,4′-dimethoxy-4,5′,6′-trihydroxychalcone and a flavone, luteolin (3′,4′,5,7-Tetrahydroxyflavone) possess XO inhibitory activity with IC 50 values of 0.21 and 2.18 µM, respectively. The L–B plots demonstrated that chalcone exhibited mixed-type inhibition, whereas luteolin exhibited competitive inhibition [ 41 ]. Furthermore, flavonone, ((2S)-5,7-dimethoxy-8,4′-dihydroxyflavanone); coumarin, esculetin (6,7-dihydroxycoumarin); and scutellarein, (4′,5,6,7-Tetrahydroxyflavone) also exhibited good XO inhibitory activities with IC50 values of 18.44, 32.56, and 48.66 µM, respectively.…”
Section: Biological Functions Of P Frutescensmentioning
confidence: 99%